Development and validation of an ELISA for quantitation of Bovine Viral Diarrhea Virus antigen in the critical stages of vaccine production - Pecora, Andrea (2009)
Bovine Viral Diarrhea Virus (BVDV) is the causative agent of a worldwide disease. The virus infects bovines of all ages, causing reproductive problems and contaminating biological products of high commercial value. The large-scale production of BVDV vaccines presents the challenge of processing antigenic proteins that are highly susceptible to the processing environment. Potency testing requires the immunization of cattle in order to determine the neutralizing antibodies titers induced by the vaccine. An alternative to the in vivo test is an in vitro measurement of key viral antigens. This paper describes the development and validation of a sandwich-type indirect ELISA that is able to detect and quantify BVDV E2 glycoprotein in live and inactivated BVDV. Validation parameters such as repeatability, intermediate precision, and reproducibility indicated that the developed ELISA constitutes an advanced tool for evaluating the BVDV antigen throughout manufacturing and vaccine release testing.